Minimum Variance Signal Selection for Aorta Radius Estimation Using Radar. (30th June 2010) - Solberg Solberg, Lars Erik Lars Erik; Hamran Hamran, Svein-Erik Svein-Erik; Berger Berger, Tor Tor; Balasingham Balasingham, Ilangko Ilangko
Abstract : This paper studies the optimum signal choice for the estimation of the aortic blood pressure via aorta radius, using a monostatic radar configuration. The method involves developing the Cramér-Rao lower bound (CRLB) for a simplified model. The CRLB for model parameters are compared with simulation results using a grid-based approach for estimation. The CRLBs are within the 99% confidence intervals for all chosen parameter values. The CRLBs show an optimal region within an ellipsoid centered at 1 GHz center frequency and 1.25 GHz bandwidth with axes of 0.5 GHz and 1 GHz, respectively. Calculations show that emitted signal energy to received noise spectral density should exceed 10 12 for a precision of approximately 0.1 mm for a large range of model parameters. This implies a minimum average power of 0.4 μ W . These values are based on optimistic assumptions. Reflections, improved propagation model, true receiver noise, and parameter ranges should be considered in a practical implementation.